2016
DOI: 10.1016/j.molonc.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Methylisoindigo preferentially kills cancer stem cells by interfering cell metabolism via inhibition of LKB1 and activation of AMPK in PDACs

Abstract: 0 AMP-activated protein kinase; CHK2, check point kinase 2; DM, Dorsomorphin; ESA, epithelial cell adhesion molecule; GSH, glutathione; HSP27, heat shock protein 2; LKB1, liver kinase B1;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 75 publications
(147 reference statements)
2
46
0
Order By: Relevance
“…Recent studies found that meisoindigo can preferentially kill cancer stem cells by interfering cell metabolism via inhibition of LKB1 and activation of AMPK in PanC . Similar results have also been drawn from metformin, which influences PanC progression by activating the LKB1‐AMPK pathway, including inhibition of cell division, promotion of apoptosis, and autophagy, downregulation of circulating insulin, and activation of the immune system …”
Section: Introductionsupporting
confidence: 57%
“…Recent studies found that meisoindigo can preferentially kill cancer stem cells by interfering cell metabolism via inhibition of LKB1 and activation of AMPK in PanC . Similar results have also been drawn from metformin, which influences PanC progression by activating the LKB1‐AMPK pathway, including inhibition of cell division, promotion of apoptosis, and autophagy, downregulation of circulating insulin, and activation of the immune system …”
Section: Introductionsupporting
confidence: 57%
“…We first studied bortezomib-induced cell death in an apoptotic assay using annexin v/PI staining 29, 30 and confirmed that apoptosis occurred in both cell lines within 24 hrs of treatment (Fig. 1D).…”
Section: Resultsmentioning
confidence: 63%
“…The blots were detected with ECL solution as previously reported 29, 30 . 40 µg of total protein was resolved on 10% SDS-PAGE gels and immunoblotted with specific antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Meisoindigo is significantly more resistant to protein kinases and exhibits higher antitumor activity than indirubin. Meisoindigo has numerous biological effects, including anti-neoplastic (Cheng et al, 2016), anti-inflammatory (Zhang et al, 2013) and antileukocyte chemotactic effects (Ye et al, 2017). However, whether meisoindigo exerts a neuroprotective action in ischemic stroke remains unknown.…”
Section: Introductionmentioning
confidence: 99%